2022
DOI: 10.1021/acs.bioconjchem.2c00197
|View full text |Cite
|
Sign up to set email alerts
|

DNA Origami–Platelet Adducts: Nanoconstruct Binding without Platelet Activation

Abstract: Objective. Platelets are small, mechanosensitive blood cells responsible for maintaining vascular integrity and activatable on demand to limit bleeding and facilitate thrombosis. While circulating in the blood, platelets are exposed to a range of mechanical and chemical stimuli, with the platelet membrane being the primary interface and transducer of outside-in signaling. Sensing and modulating these interface signals would be useful to study mechanochemical interactions; yet, to date, no methods have been def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…In sheared platelets, the number of secretory granules greatly decreased, with the remaining granules grouped together and closely colocalized with the open canalicular system, indicating ongoing degranulation. 98,102 It was previously reported that similar morphological changes accompanied PDMP formation in response to activation by strong biochemical agonists. 103 Microvesiculation induced by thrombin and calcium ionophore was associated with filopodia formation, dilatation of the open canalicular system, degranulation, and cell defragmentation.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In sheared platelets, the number of secretory granules greatly decreased, with the remaining granules grouped together and closely colocalized with the open canalicular system, indicating ongoing degranulation. 98,102 It was previously reported that similar morphological changes accompanied PDMP formation in response to activation by strong biochemical agonists. 103 Microvesiculation induced by thrombin and calcium ionophore was associated with filopodia formation, dilatation of the open canalicular system, degranulation, and cell defragmentation.…”
Section: Discussionmentioning
confidence: 74%
“…The arbitrary density of receptor distribution on the platelet surface was calculated by normalizing the fluorescence intensity (MFI) of platelet or microparticle to their forward scatter (MFS), a well-known flow cytometric parameter indicating particle size. 37, 98 In Figures S2 & S3 , alterations of fluorescence intensity, size, and receptor density with shear exposure or sonication are reported. Shear stress did not largely affect CD41 and CD42a fluorescence intensity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transmission electron microscopy (TEM) analysis confirmed that platelets displayed typical size heterogeneity and a discoid or spherical shape ( Figure 1 C). Platelets with elongated cell membrane projections and with a decrease in platelet size compared to resting platelets were also observed, which is typical of activated platelets [ 15 , 42 ].…”
Section: Resultsmentioning
confidence: 99%